The immunostimulant activity of Tibb an-Nabawi natural products: a literature review - Sani Ega Priani (Jurnal Ilmiah Farmasi, 2021)
Abstract Background: Enhancing the immune system is very important during the Covid-19 pandemic to prevent infections and reduce the risk of disease severity. Therefore, it is necessary to use natural products with an immunostimulant effect. In Islam, there is a system of treatment or disease prevention based on Al-Quran and Hadith, which is called Tibb an-Nabawi or prophetic medicine. Objective: This research aims to conduct a literature study of Tibb an-Nabawi, which has proved to be able to increase the immune system, based on Islamic and scientific approaches.Method: The research was based on a systematic literature review using research articles from the last ten years. The inclusion criteria were articles discussing the immunostimulatory activity of Tibb an-Nabawi, while the exclusion criteria were immune system enhancing herbs that were not Tibb an-Nabawi.Results: Based on the literature studies, it is known that at least six natural products based on Tibb an-Nabawi have scientifically proved to increase the immune system, namely black cumin, honey, dates, ginger, garlic, and pumpkin. The mechanism of immune system enhancement is different in each substance, but in general, they can increase humoral or cellular immunity. The active compounds contained in each of these ingredients contribute to the resulting immunostimulant activity.Conclusion: Black cumin, honey, dates, ginger, garlic, and pumpkin are natural products based on Al-Quran and Hadith, which have scientifically proved to enhance the immune system.Keywords: Tibb an-Nabawi, Thibbun Nabawi, immune system, immunostimulant, pandemic Intisari  Latar belakang:  Peningkatan sistem imun sangat penting di masa pandemic Covid-19 untuk mencegah infeksi dan menurunkan resiko keparahan penyakit. Oleh karena itu, penggunaan bahan alam dengan efek meningkatkan aktivitas sistem imun perlu dilakukan. Dalam Islam dikenal istilah thibbun Nabawi yakni pengobatan atau pencegahan penyakit berbasis Al-Quran dan Hadist.Tujuan: Melakukan studi literatur tentang bahan thibbun Nabawi yang terbukti meningkatkan sistem imun disertai kajian dari sisi Islami dan juga ilmiahnya.Metode: Penelitian berbasis systematic literature review, dengan menggunakan artikel penelitian 10 tahun terakhir. Kriteria inklusi meliputi artikel-artikel membahas aktivitas imunostimulan dari bahan-bahan thibbun Nabawi dan kriteria eksklusi adalah bahan alami peningkat sistem imun yang bukan merupakan thibbun Nabawi. Hasil: Berdasarkan studi literatur diketahui bahwa sedikitnya ada 6 bahan thibbun Nabawi yang terbukti secara ilmiah mampu meningkatkan sistem imun yakni jintan hitam, madu, kurma, jahe, bawang putih, dan labu kuning. Mekanisme peningkatkan sistem imun berbeda beda untuk setiap bahan namun secara umum bahan bahan tersebut mampu meningkatkan imunitas humoral ataupun selular. Senyawa aktif yang terkandung dalam setiap bahan tersebut berkontribusi terhadap aktivitas immunostimulant yang dihasilkanKesimpulan: Jintan hitam, madu, kurma, jahe, bawang putih, dan labu kuning merupakan bahan alam berbasis thibbun Nabawi yang terbukti secara ilmiah mampu meningkatkan system imun.Kata kunci : Thibbun Nabawi, sistem imun, imunostimulan, pandemik